Usaha Pencegahan Perceraian Dalam Gereja - Zakharia Suparyadi (Sekola Tinggi Teologi Sangkakala Jakarta, 2020)
This study aims to determine, test and prove the congregation's understanding of divorce prevention efforts in the church. The results of the data analysis show that, First: